Validation and application of the small sample punch test for toughness measurement of steels - Hlupo, Andrew (Department of Mechanical Engineering, 2025)
Power generation plants and utilities are ideally supposed to last for decades, thus there is need for suitable and innovative analytic methods that enhance the life of these vital components. The integrity, efficiency, and capacity of these components is impaired by damage mechanisms like creep and embrittlement which in turn affect the safety and operation of the power generating plants. The quasi-non-destructive small punch test (SPT) method was developed to determine the integrity and mechanical properties of materials with use of minimal material removal from components being examined, improving on the conventional mechanical test methods which require a substantial amount of material for analysis. Numerous attempts have been made to examine, validate, and interpret the data and information that is obtained from SPTs, resulting in various methods and approaches adopted. Previous work has failed to provide a less complex and more straightforward interpretation of the inhomogeneous and multiaxial stress and deformation distribution in an SPT sample during and after testing. A key concern in proving the reliability of the SPT is the determination of the onset of cracking during the test, hence the introduction of Digital Image Correlation (DIC) to advance the crack detection. The SPT method, carried out with a rig designed and built in the CME at UCT, was then validated using an “off the shelf” material whose properties could be reliably determined using conventional mechanical test techniques. The material underwent carefully controlled and repeatable heat treatments to obtain the required range in toughness properties from the same material. The tensile test, fracture toughness test and the Charpy V-Notch (CVN) test were conducted on MACSTEEL VRN 500, a high hardness low alloy martensitic steel grade which was heat treated in order to demonstrate high, medium, and low fracture toughness properties. The results from these conventional mechanical tests were characterised reliably, then correlated with the findings from the SPT technique using arithmetic and empirical correlations which exhibited high goodness of fit values. The use of DIC and the Dantec Istra 4D software on the SPTs was adopted and utilised to characterise the data that was obtained from the test further, allowing the observation of both the top surface (deflection with DIC) and bottom surface in contact with the SPT punch (displacement). A combination of DIC and strain energy density (SED) analysis was employed to detect the crack initiation on the specimen surface. The results from this study demonstrated the effectiveness of using the SPT method as a suitable quasi-non-destructive method to evaluate mechanical properties, including yield strength, ultimate tensile strength and toughness of steel structures, using small specimen samples.